2020
DOI: 10.1007/s10815-020-01913-4
|View full text |Cite
|
Sign up to set email alerts
|

PICSI vs. MACS for abnormal sperm DNA fragmentation ICSI cases: a prospective randomized trial

Abstract: Purpose To know which sperm selection technique, physiological intracytoplasmic sperm injection (PICSI) or magneticactivated cell sorting (MACS), is better for the selection of sperm with abnormal sperm DNA fragmentation (SDF) in patients undergoing intracytoplasmic sperm injection (ICSI). Methods A prospective randomized trial included 413 ICSI cases with abnormal SDF (> 20.3%) by TUNEL assay. Patients with at least 1 million total progressive motile sperm count were randomized to PICSI or MACS groups on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Subgroup analysis showed that female patients younger than 30 years in the MACS group (n ¼ 86) had significantly higher clinical pregnancy (73.9 vs. 58.3%, p ¼ 0.03) and ongoing pregnancy rates (69.5 vs. 51.3%, p ¼ 0.015) than PICSI (n ¼ 83). 48 Contrastingly, female patients between 30 and 35 years of age in the PICSI group (n ¼ 110) showed a nonsignificant increase in implantation (33.3 vs. 46%, p ¼ 0.05), clinical pregnancy (53.2 vs. 64.7%, p ¼ 0.07), and ongoing pregnancy rates (47.8 vs. 58.8%, p ¼ 0.09) compared with MACS (n ¼ 117). The most recent Cochrane study has concluded that current evidence from randomized controlled trials is low quality, and no conclusions can be drawn as to whether MACS improves live birth, clinical pregnancy, or miscarriage rates.…”
Section: Magnetic-activated Cell Sortingmentioning
confidence: 99%
“…Subgroup analysis showed that female patients younger than 30 years in the MACS group (n ¼ 86) had significantly higher clinical pregnancy (73.9 vs. 58.3%, p ¼ 0.03) and ongoing pregnancy rates (69.5 vs. 51.3%, p ¼ 0.015) than PICSI (n ¼ 83). 48 Contrastingly, female patients between 30 and 35 years of age in the PICSI group (n ¼ 110) showed a nonsignificant increase in implantation (33.3 vs. 46%, p ¼ 0.05), clinical pregnancy (53.2 vs. 64.7%, p ¼ 0.07), and ongoing pregnancy rates (47.8 vs. 58.8%, p ¼ 0.09) compared with MACS (n ¼ 117). The most recent Cochrane study has concluded that current evidence from randomized controlled trials is low quality, and no conclusions can be drawn as to whether MACS improves live birth, clinical pregnancy, or miscarriage rates.…”
Section: Magnetic-activated Cell Sortingmentioning
confidence: 99%
“…❖ Physiologic ICSI (P-ICSI): uses hyaluronic acid binding to choose mature sperm which were found to contain significantly lower SDF compared to initial unprocessed sperm (5.3% vs. 16.5%; P<0.001) ( 129 ). When compared to MACS, no significant differences were found for implantation, clinical pregnancy, and ongoing pregnancy rates overall, but when stratified for female age, outcomes were better when P-ICSI was used for women older than 30 versus MACS, although not statistically significant ( 130 ).…”
Section: Management Of Elevated Sdfmentioning
confidence: 86%
“…When comparing PICSI vs. magnetic-activated cell sorting (MACS) for abnormal sperm DNA fragmentation ICSI cases Hasanen et al 2018 (23), in their clincal trial found that PICSI and MACS are efficient techniques for sperm selection in cases with abnormal sperm DNA fragmentation. However, MACS is preferred when the females are younger than 30 years, while PICSI is preferred in older females.…”
Section: Discussionmentioning
confidence: 99%